Miss Dior a story of courage and couture - Picardie, Justine 1961- (Farrar, Straus and Giroux, 2021)
"A biography of Catherine Dior, Christian Dior's younger sister, that illuminates the work of the most iconic designer of the postwar world-her brother, Christian-and casts new light on the overlooked life of a quietly courageous, quietly extraordinary woman"--
"Originally published in 2021 by Faber & Faber Limited, Great Britain"--Title page verso
Keywords: Dior, Catherine -- 1917-2008; Dior, Catherine / 1917-2008; Dior, Christian / Family; World War, 1939-1945 / Underground movements / France / Biography; France / Biography; Dior, Christian; Families; Underground movements, War; France; 1939-1945; Biographies; Biografie